Measuring the concentration of Suspended Particulate Matter and some heavy metals in air of two areas of Rusafa in Baghdad - N. A.Al-Azzawi, Muhammad; H.H.Al-Dulaimi, Shaimaa (Iraqi Journal of Science, 2023)
This study aimed to detect the present levels and distribution of air pollutants such as SPM, Pb, Cr, Cd , and Ni , in two urban sites within Al- Rusafa side in Baghdad city (Al-Waziriya as industrial site and Al-Andalus square as commercial site). Measurements were carried out from November 2013 until June 2014. SPM, Pb, Cr, Cd , and Ni were measured using Air intake device(Sniffer) . The average minimum concentrations of SPM, Pb, Cr, Cd , and Ni were 588 μg/m3, 2.8 μg/m3, 15.6 μg/m3, 0.1 μg/m3, and 6.3 μg/m3. While the average maximum concentrations were 723 μg/m3 , 3.4 μg/m3 , 21.7 μg/m3 , 0.125 μg/m3 , and 6.8 μg/m3 , respectively. The results indicate that commercial site was more polluted with SPM , Pb , and Ni compared to the industrial site, while Cr and Cd concentrations were high in industrial site .